Analysis of combining ability and heterotic estimation on a complete Diallel cross involving five strains of common carp (Cyprinus carpio) from different geographical regions in West Java, Indonesia. (31st October 2022) - Ariyanto, Didik; Carman, Odang; Sulistyowati, Dinar T.; Zairin, Muhammad; Syukur, Muhamad; Suharyanto; Himawan, Yogi; Palimirmo, Fandrianto S.
Abstract: Decline in growth performance of Indonesian common carp was suspected due to the high rate of inbreeding. This condition requires a breeding programme to improve the genetic quality of the fish. This study was conducted to evaluate the combining ability and to estimate the value of heterotic in the hybridization of common carp. Five strains of common carp were crossed using a complete diallel cross design to obtain five pure lines, 10 F1 crossings and 10 reciprocals. Each cross was cultured separately for 3 months in net‐cage pond using a complete randomized design with three replications. All fish were fed twice a day at 3% of biomass with commercial pellet feed containing 28% crude protein. In the terminated period, 30 samples of each cross were measured and weighted to analyse the general and specific combining ability, and the heterosis. The results showed that Rajadanu and Sutisna strains have positive general combining ability (GCA), indicating these two strains have a high potential to be used as parent in the development of a hybrid population. Furthermore, the result of hybridization using one of these two strains generally produced a high positive specific combining ability (SCA) and heterosis. This study revealed that the non‐additive, especially the dominant genetic variance more affected the expression of phenotypic characters of common carp. It implicates that the breeding programme to improve the genetics of common carp could be conducted through hybridization.